Legal aspects of corporate systems for preventing cybercrime among personnel. - Dong, Bo; Chernov, Sergei; Akpinar, Kevser Ovaz (Crime, Law & Social Change, 2024)
The activities of enterprise employees can become a risk factor in terms of cybercrime, which is often associated with their lack of preparedness to counter potential cyber threats. Many businesses need a well-adjusted system of approaches to protect their internal data from all sorts of cyber threats. The objectives of the study are to analyze the practices of using systems to combat cybercrime phenomena in the corporate sphere. This analysis includes a review of the use of preventive measures by the personnel of top high-tech companies such as Apple and Samsung. The research implies to study the regulatory component of corporate systems for preventing cybercrime among personnel in the context of existing practices and approaches to the legal regulation of this issue. The study examines the relationship of corporate instructions in the field of cybersecurity. The results of the study indicate that the regulatory basis of countering internal cybercrime and data breach issues, as well as practical measures for its implementation cannot be equated, since the latter may have the nature of informal measures and do not contain formal reporting.